Evaluation of parameters to determine the degree of coal dust explosibility (2014)
Coal dust is highly explosive and caused dozens of victims in Colombia. In this research the most important and direct influence on coal dust, especially those that cause combustion and explosion inside the mine factors were analyzed; is important to discuss the characteristics of each coal mined and processed, for actions that do not compromise the integrity of the staff or facilities. Four (4) channel samples of coal exploitation faces with High Volatile Bituminous C from Cerrejón Formation were collected and analyzed: Proximal (moisture, ash, volatile matter, fixed carbon, total sulfur and calorific value ); petrographic (maceral counting and vitrinite reflectance) and Hardgrove mill index. The samples were crushed to obtain fractions corresponding to meshes 200, 270 and 325 considering those sizes could give greater risks of explosion. The analysis showed that there is a direct relationship between the results of the Hardgrove mill index and the degree of explosiveness in the fraction corresponding to 200 mesh, meaning that a higher rate of milling the greater the degree of explosiveness; a direct relationship between calorific inertinite content range and also observed. The 325 mesh fraction for all samples showed the same degree of explosiveness, which indicates that the grain size and the type of coal maceral not influence the content and coal rank. The flash point decreased for finer grains for all samples. Thus, the size of carbon particle is very important as an indicator in the coal-dust explosion factor: finer particles have greater the likelihood of explosion. The percentage of inertinites has a close relationship with the explosivity index, the higher the content of this maceral, coupled with the fine grain, coal dust behaves like a highly explosive element and generate risks in mining operations. Coal rank is an important factor regard to self combustion and explosion of particles with grain sizes greater 200 mesh. If a low rank coal has susceptible and unstable at high temperature elements and this is combined with high volatile matter and some other influential environmental parameters, such as blow air, dust concentration, humidity, and pressure, among others, the ideal combustion and then a likely violent explosion may affect a large portion of mine.